The impact of community care services on older people’s psychological health: an empirical study in Liaoning Province, China - Sen, Qin; Lei, Zhang (Frontiers in Public Health, 2023)
Background: Rapid population aging in China means it is imperative to establish a comprehensive care service system for older people. Currently, China is vigorously promoting the development of community care services for older people which should, ideally, focus on psychological health in addition to physical health. This study examined the impact of community care services on older people's psychological health.Methods: Survey data (n=741) were collected from people aged 60 years and older in Liaoning Province, China, in which various community care services for older people were provided.Information was collected regarding the types of services provided (e.g., meal services, medical and social care), participants' demographic details (age, gender, economic circumstances, etc.), and their psychological health (e.g., loneliness, life satisfaction). The impact of the various care services on older people's psychological health was subsequently examined through the construction of a structural equation model.Community care services for older people had a significant positive impact on their psychological health, with the most significant positive impact on cultural and sports activities, visiting and chat services, and emotional counseling. The impact of community care services on sub-groups of older people (e.g., those who were disabled, socially isolated and/or poor) was different.It is necessary to provide comprehensive and high-quality community care services, organize diverse cultural, sports, and recreational activities, provide differentiated and specific services for older people, and formulate corresponding service guidelines.